1996
DOI: 10.1007/s004010050407
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ubiquitin-like immunoreactivity in axons after compression trauma to rat spinal cord

Abstract: The ubiquitin-mediated proteolytic pathway is an important mode of protein degradation in various tissues. Since breakdown of proteins may occur in axons after injury we evaluated the presence of ubiquitin-like immunoreactive material in rat spinal cord following compression injury of mild, moderate and severe degrees at T8-9 level, resulting in no neurological deficit, reversible paraparesis and paraplegia of the hind limbs, respectively. Rats with mild to severe compression injury surviving 1-4 days showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Reactive axonal swelling is one characteristic property of many neuropathological processes, particularly after trauma to the brain or spinal cord (1, 8, 14, 15, 20-22). We and other groups have previously shown that such swellings contain immunoreactivity to ubiquitin (2,16,19,23). Our present demonstration of PGP 9.5 immunoreactivity in axonal swellings following lesions to the human spinal cord indicates that this enzyme is present in the swellings and can facilitate the utilization of ubiquitin in the degradation of proteins.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Reactive axonal swelling is one characteristic property of many neuropathological processes, particularly after trauma to the brain or spinal cord (1, 8, 14, 15, 20-22). We and other groups have previously shown that such swellings contain immunoreactivity to ubiquitin (2,16,19,23). Our present demonstration of PGP 9.5 immunoreactivity in axonal swellings following lesions to the human spinal cord indicates that this enzyme is present in the swellings and can facilitate the utilization of ubiquitin in the degradation of proteins.…”
Section: Discussionsupporting
confidence: 65%
“…The temporal evolution of PGP 9.5 accumulation in axonal swellings of the human spinal cord cannot be assessed in our autopsy material. However, like ubiquitin, PGP 9.5 immunoreactivity quickly accumulates in axonal swellings following compression of rat spinal cord (16,17). Even after a mild compression trauma to rat spinal cord such immunoreactivity can be detected 4 h after injury (17).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitinated deposits accumulate in Alzheimer's disease neuritic plaques (20), Parkinson's disease Lewy bodies (21), and in the intranuclear inclusion bodies of polyglutamine diseases Huntington's chorea (22) and SCA1 (23). In the axon, ubiquitin accumulates in four-repeat tau transgenic mice (24) and following spinal cord injury (25). These reports suggest that the ubiquitin proteolytic pathway plays an important role in axonal degeneration as well as in neurodegeneration in general.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence indicates that the UPS also plays a role in the recovery from SCI (Coleman and Perry, 2002 ). While the accumulation/aggregation of ubiquitinated protein is a biomarker in the early response to SCI due to the impairment of proteasome function (Li and Farooque, 1996 ; Myeku et al, 2012 ), an increase in ubiquitin levels is essential for neuronal regeneration after SCI (Schwartz and Ciechanover, 2009 ; Noor et al, 2011 ). Furthermore, the UPS also has a role in neuronal development, differentiation, and programming of neuro-stem and neuroprogenitor cells.…”
Section: Introductionmentioning
confidence: 99%